Correction: A toxicology-informed, safer by design approach for the fabrication of transparent electrodes based on silver nanowires. Issue 2 (22nd January 2019) - Toybou, Djadidi; Celle, Caroline; Aude-Garcia, Catherine; Rabilloud, Thierry; Simonato, Jean-Pierre
Abstract : Correction for 'A toxicology-informed, safer by design approach for the fabrication of transparent electrodes based on silver nanowires' by Djadidi Toybou et al., Environ. Sci.: Nano, 2019, DOI: ;10.1039/c8en00890f .